PERILAKU KONSUMSI MAHASISWA UNIVERSITAS LAMPUNG TERHADAP KOPI BUBUK INSTAN SIAP SAJI - Lutfi Yulisa; Yaktiworo Indriani; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
The purposes of this research are to analyze factors affecting purchasing decision process and attitudes on evaluation of various brands of instant coffee powder.  The research samples were 99 students, selected from four faculties of the University of Lampung, who were met at the break time and agreed to be interviewed using questionnaires.  Data were analyzed using principal component analysis and Fishbeinmulti-atribute attitude analysis.  The results of this research showed that Torabika is the instant coffee powder brand was the most widely purchased, followed by Luwak White Koffie, Nescafe, Good Day, Kapal Api, ABC, and Indocafe. The results of factor analysis showed that the fourteen expected variables influenced the purchasing decision of instant coffee powder could be reduced into four main components.  The first principal component (internal factors) consists of aroma, flavor, consistency, and creamer.  The second principal components (external factors) consist of brand, advertising, pricing, and bonuses.  The third principal component (benefit factors) consists of reducing drowsiness and suitability of drinking with other food variables.  The fourth principal component (factors of excellence) consists of a non-pulpy, easily obtained.  Based on the evaluation of the consumer attitude variables, it showed that although the consumption of ABC brand was the least but it got the highest attitude value compared to other brands. If the attitudes of the students were sorted, ratings of the highest student attitudes were ABC, Nescafe, followed by Luwak White Koffie, Torabika, and Good Day.Key words: factor analysis, principal component analysis, analysis of Fishbein attitude, instant coffee